PSYCHOLOGICAL FOUNDATIONS OF THE MORAL QUALITIES OF A LEADER IN DECISION-MAKING - Nazarov A. S.; Mitina O.V. (Journal Park Publishing, 2023)
This article analyzes the ethnopsychological features of managerial decision-making. The article also describes the leader and his personal responsibility in making decisions.
Keywords: personality, management, managerial decisions, decision making, manager, ethnopsychological characteristics.